Development of Optimal Energy Storage System Sizing Algorithm for Photovoltaic Supplier in South Korea - Oh, Seongmun; Kong, Junhyuk; Lee, Wonjun; Jung, Jaesung (IEEE Power and Energy Society General Meeting, 2018)
The South Korean government makes huge efforts to accelerate the utilization of Energy Storage System (ESS) along with renewable energy generation. In this manner, this paper presents the optimal ESS sizing algorithm for Photovoltaic (PV) supplier under current government policy and compensation rule. This algorithm determines if the installation of ESS is beneficial and then, suggests the optimal size of ESS to maximize the revenue when PV generator combines with ESS. The actual PV generation profiles are used to verify the effectiveness of the proposed algorithm.
Keywords: Energy storage systems; Korean Government; Optimal energy; Optimal ESS Sizing; Renewable energy certificates; Renewable energy generation; Sizing algorithms; System marginal price; Energy Storage System (ESS); Optimal ESS Sizing; Renewable Energy Certificate (REC); System Marginal Price (SMP)